Gambaran kepatuhan minum obat dan kontrol ulang pada peserta Prolanis diabetes mellitus dan hipertensi di Puskesmas Bailang Kota Manado - Rifai, Chaerunnisa; Siagian, Iyone Esra Tiurma; Sapulete, Margareth Rosalinda (UNIVERSITAS SAM RATULANGI, 2025)
Background: Non-communicable diseases cause the most deaths worldwide. In 2024, Manado City had 11,677 cases of diabetes mellitus (DM) and 43,368 cases of hypertension. Adherence to treatment is an indicator of successful disease management, but national research found that drug compliance and recontrol for DM and hypertension patients remain low. The control and management of diabetes and hypertension are the main focus of Prolanis, but some studies on Prolanis have found high levels of non-compliance, so researchers examined drug compliance and recontrol. Aim: To provide an overview of a drug compliance and recontrol of Prolanis participants with DM and hypertension at the Bailang Public Health Center in Manado City. Methods: Descriptive quantitative approach and a cross-sectional design involving 41 Prolanis DM and 55 Prolanis hypertension at the Bailang Public Health Center in Manado City. The questionnaire used is the SKI 2023. Results: Prolanis DM participants found that 29 people (90.6%) demonstrated drug compliance as directed by their doctor, while 3 people (9.4%) were non-compliant. A total of 31 people (96.9%) attended recontrol regularly, while 1 person (3.1%) attended only occasionally. Prolanis participants with hypertension found that 50 people (90.9%) demonstrated regular drug compliance, while 5 people (9.1%) took their medication irregularly. A total of 51 people (92.7%) attended recontrol regularly, whereas 4 participants (7.3%) did so only occasionally. Conclusion: Prolanis participants with DM and hypertension at the Bailang Public Health Center in Manado City were categorized as compliant with drug therapy and regular in recontrol as directed by their doctor.